Fast route model in peer to peer network - CHEN Shan-xiong 1; LI Li1; ZHANG Lin1 (Tongxin xuebao)
A fast self-organizing routing model（FSRM） was proposed based on DHT.In the model,the approach of the route lookup,the system of nodes joining and leaving was described.When joining node need to select neighboring nodes,measured scheme of stability threshold ensure that the peer to peer network fast routing and convergence.The simulation results of the model performance are analyzed to prove the convergence time,node querying speed and adaptability to churn are better than the traditional model.